Effects of visual blur on microsaccades during visual exploration - Sherry Tang; Peggy Skelly; Jorge Otero-Millan; Jonathan Jacobs; Jordan Murray; Aasef G. Shaikh; Fatema F. Ghasia (Bern Open Publishing, 2019)
Microsaccades shift the image on the fovea and counteract visual fading. They also serve as an optimal sampling strategy while viewing complex visual scenes. Microsaccade production relies on the amount of retinal error or acuity demand of a visual task. The goal of this study was to assess the effects of blur induced by uncorrected refractive error on visual search. Eye movements were recorded in fourteen healthy subjects with uncorrected and corrected refractive error while they performed a) visual fixation b) blank-scene viewing c) visual search (spot the difference) tasks. Microsaccades, saccades, correctly identified differences and reaction times were analyzed. The frequency of microsaccades and correctly identified differences were lower in the uncorrected refractive error during visual search. No similar change in microsaccades was seen during blank-scene viewing and gaze holding tasks. These findings suggest that visual blur, hence the precision of an image on the fovea, has an important role in calibrating the amplitude of microsaccades during visual scanning.